2015
DOI: 10.4149/av_2015_01_40
|View full text |Cite
|
Sign up to set email alerts
|

The effect of BM67 gene deletion on Bombyx mori nuclear polyhedrosis virus replication

Abstract: Summary. -Homologs of Bombyx mori nuclear polyhedrosis virus (BmNPV) Bm67 gene ORF67 have been found in the genome of all lepidopteran nuclear polyhedrosis viruses, but their function is still not very clear. In order to analyze it we employed a bacmid harboring the complete BmNPV genome including the Bm67 gene and expressing infectious virus (wtBacmid) for the construction of its Bm67-deficient variant (Bm67-KO-Bacmid) using the Red recombination system and the Bm67-repaired variant (Bm67-Re-Bacmid) using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Many experimental studies have shown that gene knockout technology is a powerful tool for determining gene function. It has also been used to study baculovirus genes (Su et al, 2011;Lin and Blissard, 2002;Shi et al, 2015). In this study, lef-9-KO bacmids were constructed using gene knockout technology with a Red recombination system, and were used to study the effect of this defect virus on infectious virus production, and viral replication and transcription, in comparison with wild-type virus (BmNPV) and lef-9repaired virus.…”
Section: Introductionmentioning
confidence: 99%
“…Many experimental studies have shown that gene knockout technology is a powerful tool for determining gene function. It has also been used to study baculovirus genes (Su et al, 2011;Lin and Blissard, 2002;Shi et al, 2015). In this study, lef-9-KO bacmids were constructed using gene knockout technology with a Red recombination system, and were used to study the effect of this defect virus on infectious virus production, and viral replication and transcription, in comparison with wild-type virus (BmNPV) and lef-9repaired virus.…”
Section: Introductionmentioning
confidence: 99%